(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Sleeve gastrectomy is one of the most widely performed bariatric procedures due to its technical simplicity and favorable metabolic outcomes. However, postoperative complications and variable long-term results indicate the need for optimization of this surgical technique. This study aims to analyze clinical and pathomorphological approaches to optimizing sleeve gastrectomy by integrating patient-related clinical factors with structural and histological characteristics of the gastric wall. The findings demonstrate that individualized surgical planning based on gastric wall morphology, inflammatory status, vascular integrity, and regenerative capacity may significantly reduce complications and improve functional and metabolic outcomes.